Unlocking The Potential of "Kalosara": An Extensive Analysis of Adultery Instances Dispute Resolution in the Tolaki Tribe through the Lens of al-Ishlah Concept - Haq, Islamul; Hannani, Hannani; Syatar, Abdul; Amiruddin, Muhammad Majdy; Musmulyadi, Musmulyadi (Al-Risalah, 2024)
This article delves into the comprehensive examination of the dispute resolution in adultery cases within the Tolaki Tribe, specifically through the traditional practice of "Kalosara." The research also explores the relevance of Kalosara to the al-Ishlah concept in Islamic criminal law. This research uses the literature review method to establish a robust theoretical foundation. This research indicates a significant relevance between the Kalosara custom and the concept of Ishlah in the context of Islamic criminal law. The practice of Kalosara in resolving cases of adultery within the Tolaki Tribe reflects the principles of Ishlah, emphasizing reconciliation, restoration, and conflict resolution. The stages of the resolution process, from the acknowledgment of the perpetrator to the purification ceremony, mirror a holistic approach to achieving restorative justice. The research results show that the integration of Kalosara customary law in the Ishlah process reflects the aspirations of the Tolaki community for a comprehensive resolution and effective recovery at various levels, including individual, social, and broader community contexts. In the settlement through Kalosara, adulterers are expected to admit their actions, express regret, and carry out a purification process with a holistic approach to resolving conflicts and restoring social relations.